Rapid estimation of Salmonella enterica contamination level in ground beef – Application of the time-to-positivity method using a combination of molecular detection and direct plating. (February 2021) - Harhay, Dayna M.; Weinroth, Margaret D.; Bono, James L.; Harhay, Gregory P.; Bosilevac, Joseph M.
Abstract: Little progress has been made in decreasing the incidence rate of salmonellosis in the US over the past decade. Mitigating the contribution of contaminated raw meat to the salmonellosis incidence rate requires rapid methods for quantifying Salmonella, so that highly contaminated products can be removed before entering the food chain. Here we evaluated the use of Time-to-Positivity (TTP) as a rapid, semi-quantitative approach for estimating Salmonella contamination levels in ground beef. Growth rates of 14 Salmonella strains (inoculated at log 1 to −2 CFU/g) were characterized in lean ground beef mTSB enrichments and time-to-detection was determined using culture and molecular detection methods. Enrichments were sampled at five timepoints and results were used to construct a prediction model of estimated contamination level by TTP (superscript indicates time in hours) defined as TTP 4 : ≥ 5 CFU/g; TTP 6 : ≤ 5, ≥ 1 CFU/g; TTP 8 : ≤ 1, ≥ 0.01 CFU/g; with samples negative at 8 h estimated ≤ 0.01 CFU/g. Model performance measures showed high sensitivity (100%) and specificity (83% and 93% for two detection methods) for samples with a TTP 4, with false negative rates of 0%. Highlights: Time-to-Positivity sampling method can detect Salmonella levels ≥5 CFU/g in ground beef enrichments at 4 h. Direct plating with Petrifilm™ EB and replica plating to XLD provides confirmation of counts and evidence of viability. Average DT of Salmonella in enrichments was 19.5 min, however some strains grew faster with DT of 15.5 min. At low inoculation levels certain Salmonella grew poorly and were outcompeted by ground beef microflora.